Study of the interplay between lower-order and higher-order energetic strain-gradient effects in polycrystal plasticity - Christodoulou, Paul G.; Lebensohn, Ricardo A.; Beyerlein, Irene J. (Journal of the mechanics and physics of solids, 2022)
Strain-gradient (SG) plasticity refers to a class of non-local theories in which gradients of plastic slip determine the storage of geometrically necessary dislocations, introducing a length-scale dependence in the mechanical behavior of crystalline materials, which is otherwise lacking in local theories. In this work, we incorporate lower-order (LO) and higher-order energetic (HOE) strain-gradient effects into a crystal plasticity fast Fourier transform (FFT)-based formulation to investigate the interplay of the length scale that each strain-gradient term introduces at the microscale, and the mechanical properties that result at the macroscale. For an applicable range of length scales, we consider two systems: a 1-D two-phase face centered cubic (FCC) laminate and a 3-D FCC polycrystal, and two uniaxial deformation modes: monotonic tension and cyclic tension–compression. We show that increases in the individual LO and HOE length scales increase the hardening rate and strength of the material, respectively. When combined, the strong LO hardening is less pronounced than the effect alone due to the lowering of the gradients due to the HOE microstress. We demonstrate that the LO and HOE hardening manifest as “isotropic” (yield surface expansion) and “kinematic” (yield surface shift) effects, respectively, consistent with their theoretical origins. We show that in cyclic loading, the Bauschinger effect emerges in both local and non-local calculations and link its origins and severity to the behavior in the strain field, slip-system rates, and the HOE microforce. •The interplay between strain-gradient length-scale parameters is studied.•Increasing the higher-order energetic parameter increases polycrystal yield strength.•Increasing the lower-order (LO) length scale increases the strain-hardening rate.•The higher-order effect reduces gradients, limiting the influence of the LO effect.•The higher-order energetic effect enhances the local Bauschinger effect.